Physiological and biochemical responses of three grapevine genotypes to deficit irrigation - Said, Ennahli (Kansas State University, 2007)
This project investigated the physiological and biochemical responses of three grapevine genotypes to a deficit irrigation strategy termed partial rootzone drying (PRD). The principle objectives of the project were to (1) establish if the response to PRD is a unique vine physiological response; (2) to investigate the effect of PRD on berry maturation and composition; (3) effect of PRD on vine water-use efficiency; (4) investigate the hormonal signal involved in the PRD mechanism. In addition, the project investigated the adaptation of these three grapevine genotypes to Kansas climatic conditions. The irrigation project was conducted in both a greenhouse at Kansas State University, Manhattan, KS, and field conditions in an experimental vineyard at the John C. Pair Horticultural Research Center, Haysville, Kansas. The greenhouse study was replicated four times (6 months each run) and the field study ran from the 2005/2006 season through the 2006/2007 season. Application of PRD to vines resulted in a unique physiological response distinct from other established deficit irrigation procedures such as regulated deficit irrigation (RDI); however, the overall physiological responses of the vines were defined by the environmental conditions of the vineyard where the experiment occurred. Reduced water availability, low to medium vigor vines, restricted root development, and high evaporative demand were all factors in the vines response to PRD. Under these conditions, PRD did maintain the yield at deficit irrigation rates compared to fully irrigated vines, and was responsible for physiological changes in the vine that could have long-term implications for yield stability. The application of PRD resulted in an improvement in plant water status and maintenance of leaf function as measured by photosynthesis, stomatal conductance and leaf water potential throughout the season.
Keywords: vitis; deficit; Agriculture, General (0473)